Paul Valéry and his biologicist reflections about restructuring, fragility and contingency of life - Ramírez Jaramillo, John Fredy (Estudios de Filosofía, 2013)
This article analyzes the biologicist arguments through which Paul Valery interprets the phenomenon of life. To this end, we first show the creative power that nature reveals under the laws of restructuring and order which begin to be visible in the molecular structures that give shape to the universe. After that, the redefinition that the author does of the concept of material is examined in the light of the scientific findings reached in his time. Then, the characteristics essential to life are presented and determined by the complementary integration between the conservation and transformation laws of nature. In the same way we present the statements for which the phenomenon of death is taken as a characteristic of life; in the same way that the arguments for which life is considered a random product. Finally, the scarcity and finiteness of life are presented, which are explicitly stated by Valery based on evolutionist theory.